Dancing with words : helping students love language through authentic vocabulary instruction - Michaels, Judy Rowe, 1944- (Urbana, Ill. : National Council of Teachers of English, 2001)
Presents alternatives to teaching vocabulary with quizzes and work sheets, explaining how to teach the relationship between syntax and voice, discuss connotations, and use theater games, dance, poetry writing, and several other activities.
Includes bibliographical references.
Professional
Keywords: Vocabulary -- Study and teaching; Vocabulary -- Study and teaching